Factors predictive for computed tomography use and abnormality in paediatric head injuries in Australia and New Zealand. (22nd December 2020) - Wilson, Catherine L; Hearps, Stephen JC; Tavender, Emma J; Phillips, Natalie T; Lawton, Ben; Kinnear, Frances; Beattie, Amie; Mitenko, Hugh; Young, Russell; Cole, Joanne; Kochar, Amit; George, Shane; et al.
Abstract: Objectives: To investigate patient‐level factors predictive for computed tomography of the brain (CTB) use and abnormality in head injured children in Australia and New Zealand. Methods: Retrospective data from tertiary, urban/suburban and regional/rural EDs including factors predictive for CTB use and abnormality. Results: Of 3072 children at 31 EDs, 212 (6.9%) had a CTB scan, of which 66 (31%) were abnormal. Increasing age, serious mechanisms of injury and decreasing Glasgow Coma Score were predictive for ordering CTB. Decreasing age was predictive for CTB abnormalities. Other factors were not. Conclusion: Patient‐level drivers of CTB use in children in Australia and New Zealand are consistent with international data.